International organization - Rittberger, Volker , 1941-2011; Kruck, Andreas , 1981-; Zangl, Bernhard , 1967- (Palgrave Macmillan, 2012)
International organizations such as the UN, EU and IMF play an increasingly important role in international politics. Fully revised and updated, this broad-ranging text provides a systematic theoretical and empirical introduction to the structure, policies and performance of international organizations